KAJIAN BEBERAPA SIFAT FISIKA TANAH YANG DITANAMI KELAPA SAWIT PADA UMUR DAN KELERENGAN YANG BERBEDA (Studi Kasus Perkebunan Sawit Kelurahan Simpang Tuan, Kecamatan Mendahara Ulu,Tanjung Jabung Timur) - Laddy Megayanti; Zurhalena Zurhalena; Heri Junedi; Najla Anwar Fuadi (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Land clearing for oil palm plantations using heavy equipment will affect the physical properties of the soil, namely increasing soil compaction and decreasing soil porosity and soil moisture content. However, along with the growth of plantation crops such as oil palm, it is suspected that it can restore the physical properties of the soil. The aim of the study was to examine the differences in the physical characteristics of the soil at various ages of oil palm and the slope. The study was conducted in one of the oil palm plantations, Simpang Tuan Village, Mendahara Ulu District, Tanjung Jabung Timur Regency from March to May 2021. The study was carried out using the survey method, selecting representative areas using the Purposive Random Sampling method on oil palm plantation areas with various ages (newly planted, 5 years old, and 12 years old) and various marbles (0-3%, 3-8%, and 8-15%) with 3 replications. Parameters observed were soil texture, soil organic matter content, bulk density, water content, and soil permeability. The results showed that the older the age of oil palm plantations, the increase in organic matter content, total pore space, water content and soil permeability and a decrease in volume weight. The steeper the slope, the greater the weight of the soil volume and a decrease in the organic matter content, total pore space, water content and soil permeability.